INFLUÊNCIA DA TERAPIA HORMONAL ESTROPROGESTATIVA E ESTROGÊNICA SOBRE O FLUXO SALIVAR DE MULHERES NA PÓS-MENOPAUSA - Lago, Marília Leal Ferreira (2010)
Objective: Check if there are differences in salivary flow of postmenopausal women with and without estroprogestative and estrogen hormone therapy Methods: We conducted a study of case-control, composed of 86 postmenopausal women, comprising in the case group, 47 users estroprogestative or estrogen HRT, and the control group, 39 women not taking HRT. All patients underwent history taking, through the application of a standard questionnaire, followed by the realization of sialometry stimulated whole. It was used as comparative values, the normal flow from 1.0 to 3.0 mL / min flow down from 0.7 to 1.0 mL / min; hyposalivation, less than 0.7 mL / min. Data were statistically analyzed by chi-square and Student t test (p <0.05). Results: There were no statistically significant differences in the variables analyzed, except for body mass index. Conclusion: In this sample, the flow of saliva in postmenopausal women is not influenced by hormone therapy, regardless of whether estroprogestative or estrogen.